Incremental Prognostic Utility of Left Ventricular Global Longitudinal Strain in Hypertrophic Obstructive Cardiomyopathy Patients and Preserved Left Ventricular Ejection Fraction. Issue 10 (20th October 2017) - Tower‐Rader, Albree; Betancor, Jorge; Popovic, Zoran B.; Sato, Kimi; Thamilarasan, Maran; Smedira, Nicholas G.; Lever, Harry M.; Desai, Milind Y.
Abstract : Background: In obstructive hypertrophic cardiomyopathy patients with preserved left ventricular (LV) ejection fraction, we sought to determine whether LV global longitudinal strain (LV‐GLS) provided incremental prognostic utility. Methods and Results: We studied 1019 patients with documented hypertrophic cardiomyopathy (mean age, 50±12 years; 63% men) evaluated at our center between 2001 and 2011. We excluded age <18 years, maximal LV outflow tract gradient <30 mm Hg, bundle branch block or atrial fibrillation, past pacemaker/cardiac surgery, including myectomy/alcohol ablation, and obstructive coronary artery disease. Average resting LV‐GLS was measured offline on 2‐, 3‐, 4‐chamber views using Velocity Vector Imaging (Siemens, Malvern, PA). Outcome was a composite of cardiac death and appropriate internal defibrillator (implantable cardioverter defibrillator) discharge. Maximal LV thickness, LV ejection fraction, indexed left atrial dimension, rest and maximal LV outflow tract gradient, and LV‐GLS were 2.0±0.2 cm, 62±4%, 2.2±4 cm/m 2, 52±42 mm Hg, 103±36 mm Hg, and −13.6±4%. During 9.4±3 years of follow‐up, 668 (66%), 166 (16%), and 122 (20%), respectively, had myectomy, atrial fibrillation, and implantable cardioverter defibrillator implantation, whereas 69 (7%) had composite events (62 cardiac deaths). Multivariable competing risk regression analysis revealed that higher age (subhazard ratio, 1.04 [1.02–1.07]), AF during follow‐up (subhazard ratio, 1.39 [1.11–1.69]), and worsening LV‐GLS (subhazard ratio, 1.11 [1.05–1.22]) were associated with worse outcomes, whereas myectomy (subhazard ratio, 0.44 [0.25–0.72]) was associated with improved outcomes (all P <0.01). Sixty‐one percent of events occurred in patients with LV‐GLS worse than median (−13.7%). Conclusions: In obstructive hypertrophic cardiomyopathy patients with preserved LV ejection fraction, abnormal LV‐GLS was independently associated with higher events, whereas myectomy was associated with improved outcomes.